2010
DOI: 10.1002/ejic.200901194
|View full text |Cite
|
Sign up to set email alerts
|

NCN‐Chelated Organoantimony(III) and Organobismuth(III) Phosphonates: Syntheses and Structures

Abstract: The reactions of the organoantimony and organobismuth oxides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…As a part of an ongoing investigation of main group compounds containing potentially tridentate pincer-type ligands, and as a logical continuation of studies in this field, we report herein the syntheses, structures and reactivity of organoantimony and organobismuth phosphinate and phosphite complexes (Scheme 1) that are stabilized by the NCN chelating ligand L. Previously we were able to synthesize mixed phoshonate compounds (i.e. complexes containing two different phosphonate groups), [3] and herein the syntheses of novel mixed phosphinate-phosphite, phosphonate-phoshinate and phosphonate-phosphite compounds are also described (Scheme 2). Scheme 2.…”
Section: P(h)(o)][(ho) 2 P(h)-(o)]} Andmentioning
confidence: 99%
See 4 more Smart Citations
“…As a part of an ongoing investigation of main group compounds containing potentially tridentate pincer-type ligands, and as a logical continuation of studies in this field, we report herein the syntheses, structures and reactivity of organoantimony and organobismuth phosphinate and phosphite complexes (Scheme 1) that are stabilized by the NCN chelating ligand L. Previously we were able to synthesize mixed phoshonate compounds (i.e. complexes containing two different phosphonate groups), [3] and herein the syntheses of novel mixed phosphinate-phosphite, phosphonate-phoshinate and phosphonate-phosphite compounds are also described (Scheme 2). Scheme 2.…”
Section: P(h)(o)][(ho) 2 P(h)-(o)]} Andmentioning
confidence: 99%
“…Both compounds 5 and 6 contain POH groups in their structure, which was reflected by observation of three broad bands (around 2700, 2300 and 1600 cm -1 ) in their IR spectra, and splitting of the POH peaks points to strong hydrogen bonds between these POH moieties. [3,5] We have recently reported so-called mixed antimony(III) and bismuth(III) phoshonates, in which two different phosphonate units are bonded to the same central ion. [3] We have also suggested that an analogous synthetic protocol may lead to similar phosphorus-antimony(bismuth) compounds containing either two phosphorus ions in a +III oxidation state, or with one phosphorus ion in a +III state and the other in a +V state.…”
Section: Syntheses and Characterization Of Compounds 3-8mentioning
confidence: 99%
See 3 more Smart Citations